Error-free DNA damage tolerance and sister chromatid proximity during DNA replication rely on the Polα/Primase/Ctf4 Complex - Fumasoni, Marco; Zwicky, Katharina; Vanoli, Fabio; Lopes, Massimo; Branzei, Dana (Molecular cell, 2015)
Chromosomal replication is entwined with DNA damage tolerance (DDT) and chromatin structure establishment via elusive mechanisms. Here we examined how specific replication conditions affecting replisome architecture and repriming impact on DDT. We show that Saccharomyces cerevisiae Polα/Primase/Ctf4 mutants, proficient in bulk DNA replication, are defective in recombination-mediated damage-bypass by template switching (TS) and have reduced sister chromatid cohesion. The decrease in error-free DDT is accompanied by increased usage of mutagenic DDT, fork reversal, and higher rates of genome rearrangements mediated by faulty strand annealing. Notably, the DDT defects of Polα/Primase/Ctf4 mutants are not the consequence of increased sister chromatid distance, but are instead caused by altered single-stranded DNA metabolism and abnormal replication fork topology. We propose that error-free TS is driven by timely replicative helicase-coupled re-priming. Defects in this event impact on replication fork architecture and sister chromatid proximity, and represent a frequent source of chromosome lesions upon replication dysfunctions.